Drosophila ref(2)P is required for the parkin-mediated suppression of mitochondrial dysfunction in pink1 mutants. - de Castro, I.P.; Costa, A.C.; Celardo, I.; Tufi, R.; Dinsdale, D.; Loh, S.H.; Martins, L.M. (Cell death & disease, 2013)
Autophagy is a critical regulator of organellar homeostasis, particularly of mitochondria. Upon the loss of membrane potential, dysfunctional mitochondria are selectively removed by autophagy through recruitment of the E3 ligase Parkin by the PTEN-induced kinase 1 (PINK1) and subsequent ubiquitination of mitochondrial membrane proteins. Mammalian sequestrome-1 (p62/SQSTM1) is an autophagy adaptor, which has been proposed to shuttle ubiquitinated cargo for autophagic degradation downstream of Parkin. Here, we show that loss of ref(2)P, the Drosophila orthologue of mammalian P62, results in abnormalities, including mitochondrial defects and an accumulation of mitochondrial DNA with heteroplasmic mutations, correlated with locomotor defects. Furthermore, we show that expression of Ref(2)P is able to ameliorate the defects caused by loss of Pink1 and that this depends on the presence of functional Parkin. Finally, we show that both the PB1 and UBA domains of Ref(2)P are crucial for mitochondrial clustering. We conclude that Ref(2)P is a crucial downstream effector of a pathway involving Pink1 and Parkin and is responsible for the maintenance of a viable pool of cellular mitochondria by promoting their aggregation and autophagic clearance.